Understanding and addressing challenges for advance care planning in the COVID-19 pandemic: An analysis of the UK CovPall survey data from specialist palliative care services. (July 2021) - Bradshaw, Andy; Dunleavy, Lesley; Walshe, Catherine; Preston, Nancy; Cripps, Rachel L; Hocaoglu, Mevhibe; Bajwah, Sabrina; Maddocks, Matthew; Oluyase, Adejoke O; Sleeman, Katherine; Higginson, Irene J; Fraser, Lorna; et al.
Background: Specialist palliative care services play an important role in conducting advance care planning during COVID-19. Little is known about the challenges to advance care planning in this context, or the changes services made to adapt. Aim: Describe the challenges that UK specialist palliative care services experienced regarding advance care planning during COVID-19 and changes made to support timely conversations. Design: Online survey of UK palliative/hospice services' response to COVID-19. Closed-ended responses are reported descriptively. Open-ended responses were analysed using a thematic Framework approach using the Social Ecological Model to understand challenges. Respondents: Two hundred and seventy-seven services. Results: More direct advance care planning was provided by 38% of services, and 59% provided more support to others. Some challenges to advance care planning pre-dated the pandemic, whilst others were specific to/exacerbated by COVID-19. Challenges are demonstrated through six themes: complex decision making in the face of a new infectious disease; maintaining a personalised approach; COVID-19-specific communication difficulties; workload and pressure; sharing information; and national context of fear and uncertainty. Two themes demonstrate changes made to support: adapting local processes and adapting local structures. Conclusions: Professionals and healthcare providers need to ensure advance care planning is individualised by tailoring it to the values, priorities, and ethnic/cultural/religious context of each person. Policymakers need to consider how high-quality advance care planning can be resourced as a part of standard healthcare ahead of future pandemic waves. In facilitating this, we provide questions to consider at each level of the Social Ecological Model.